Proteomics Analysis of the Spinal Dorsal Horn in Diabetic Painful Neuropathy Rats With Electroacupuncture Treatment - Yu, Xiangmei; Chen, Xiaomei; Liu, Weiting; Jiang, Menghong; Wang, Zhifu; Tao, Jing (Frontiers in Endocrinology, 2021)
Clinical evidence had shown that electro-acupuncture (EA) of Zusanli (ST36) and Shenshu (BL23) is effective in relieving the diabetic painful neuropathy (DPN). However, its molecular mechanism remains to be further studied. More potential biomarkers are also needed to reveal the deeper mechanism of EA on the DPN.